Pension, fertility, and education - Volker Meier; Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2005)
A pay-as-you-go pension scheme is associated with positive externalities of having children and providing them with human capital. In a framework with heterogeneity in productivity, and stochastic and endogenous investment in fertility and education, we discuss internalization policies associated with child benefits in the pension formula. The second-best scheme displays both a benefit contingent on the contributions of children and a purely fertility-related component.
Keywords: H55; J13; J18; H23; 330; pay-as-you-go; fertility; human capital; externalities; Gesetzliche Rentenversicherung; Umlageverfahren; Externer Effekt; Fruchtbarkeit; Bildungsinvestition; Theorie